تحليل سند ومتن حديث فضل قراءة سورة الواقعة: دراسة تخريج الحديث - Rizaka, Maghza; Razi, Fahrur; Prayogi, Ananda; Hasyim, Muhammad Wahid (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
The tradition of reciting Surah al-Wāqi‘ah at night in Indonesian Islamic boarding schools reflects a deep desire to understand the Quran. However, the continuity of this practice requires a strong legal basis. This study examines the validity of hadith supporting this tradition using the Takhrīj al-Hadīth method. The main point is to ensure the credibility of the hadith chain and its textual content. The goal is to offer a more profound comprehension of the virtues of reciting Surah al-Wāqi‘ah and to evaluate the authenticity of this tradition. While this tradition holds significant educational value for students, it's crucial to strengthen its legal foundation. The research highlights that the hadith supporting this practice falls under the category of aḥād - gharīb due to its transmission through one narrator, 'Abdullah ibn Mas’ūd. However, the weakness lies in the weak ḍa‘īf (weak) status of its chain due to an unknown narrator’s reliability, Abū Ẓabyah. This study offers profound insights into religious practices and emphasizes the critical evaluation needed for traditional practices. Reciting Surah al-Wāqi‘ah remains valuable, yet understanding a strong legal basis is crucial to maintaining the authenticity of religious practices.